Analisis Laju Infiltrasi Pada Sub Das (Daerah Aliran Sungai) Siak Kota Pekanbaru (Studi Kasus: Das Senapelan Dan Das Sago) - Muhammad Habsyie Ravie; Siswanto Siswanto; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Pekanbaru city development is experiencing rapid development due to population and economic growth, this has made land use become more dense. The construction of a dense infrastructure makes the process of infiltration or absorption of water into the ground slower. As a result of the development of infrastructure, the surface runoff is large and can cause flooding. An infiltration rate study was conducted to be used as a reference for conservation measures and overcome the problem of magnitude of surface runoff. Infiltration rate measurement using a double ring infiltrometer and Horton equation analysis method is performed to determine the infiltration rate. Measurement of infiltration rate in the field is based on procedures in SNI 7752: 2012. Calculation of infiltration rate analysis aims to determine the value of infiltration capacity and infiltration rate in the area under study. At the 6 research location points, the largest infiltration capacity at the research site 2 was 90 mm / hour and the smallest infiltration capacity at the research site 3 and 6 was 30 mm / hour. Infiltration rate analysis using the Horton equation method obtained the highest infiltration rate at study point 2 which is 76.38 mm / hour and the lowest infiltration rate at research point 6 is 18 mm / hour. Classification of infiltration rate was conducted based on the analysis of the total infiltration volume, the largest value was at point 4 at 27.46 mm with a constant decrease time at 1.67 hours and the smallest infiltration volume value was at point 6 at 12.73 mm with a time of constant decrease at 1.17 hours. Based on the U.S. Soil Conservation, at 6 testing points has infiltration rate which is rather slow and moderate.Keywords: infiltration, horton’s method, surface runoff